Bap, a biofilm matrix protein of Staphylococcus aureus prevents cellular internalization through binding to GP96 host receptor. - Jaione Valle; Cristina Latasa; Carmen Gil; Alejandro Toledo-Arana; Cristina Solano; José R Penadés; Iñigo Lasa (PLoS Pathogens)
The biofilm matrix, composed of exopolysaccharides, proteins, nucleic acids and lipids, plays a well-known role as a defence structure, protecting bacteria from the host immune system and antimicrobial therapy. However, little is known about its responsibility in the interaction of biofilm cells with host tissues. Staphylococcus aureus, a leading cause of biofilm-associated chronic infections, is able to develop a biofilm built on a proteinaceous Bap-mediated matrix. Here, we used the Bap protein as a model to investigate the role that components of the biofilm matrix play in the interaction of S. aureus with host cells. The results show that Bap promotes the adhesion but prevents the entry of S. aureus into epithelial cells. A broad analysis of potential interaction partners for Bap using ligand overlayer immunoblotting, immunoprecipitation with purified Bap and pull down with intact bacteria, identified a direct binding between Bap and Gp96/GRP94/Hsp90 protein. The interaction of Bap with Gp96 provokes a significant reduction in the capacity of S. aureus to invade epithelial cells by interfering with the fibronectin binding protein invasion pathway. Consistent with these results, Bap deficient bacteria displayed an enhanced capacity to invade mammary gland epithelial cells in a lactating mice mastitis model. Our observations begin to elucidate the mechanisms by which components of the biofilm matrix can facilitate the colonization of host tissues and the establishment of persistent infections.